Production of New Microbially Conjugated Bile Acids by Human Gut Microbiota - Garcia, Carlos J; Kosek, Vit; Beltrán, David; Tomás-Barberán, Francisco A; Hajslova, Jana (Biomolecules, 2022)
Gut microbes have been recognized to convert human bile acids by deconjugation, dehydroxylation, dehydrogenation, and epimerization of the cholesterol core, but the ability to re-conjugate them with amino acids as an additional conversion has been recently described. These new bile acids are known as microbially conjugated bile acids (MCBAs). The aim of this study was to evaluate the MCBAs diversity produced by the gut microbiota through a metabolomics approach. In this study, fresh fecal samples from healthy donors were evaluated to explore the re-conjugation of chenodeoxycholic and 3-oxo-chenodeoxycholic acids by the human gut microbiota. No significant differences were found between the conversion trend of both BAs incubations. The in vitro results showed a clear trend to first accumulate the epimer isoursochenodeoxycholic acid and the dehydroxylated lithocholic acid derivatives in samples incubated with chenodeoxycholic and 3-oxo-chenodeoxycholic acid. They also showed a strong trend for the production of microbially conjugated dehydroxylated bile acids instead of chenodeoxycholic backbone conjugates. Different molecules and isomers of MCBAs were identified, and the new ones, valolithocholate ester and leucolithocholate ester, were identified and confirmed by MS/MS. These results document the gut microbiota's capability to produce esters of MCBAs on hydroxyls of the sterol backbone in addition to amides at the C24 acyl site. This study opens a new perspective to study the BAs diversity produced by the human gut microbiota.
Keywords: Gastrointestinal Microbiome; Humans; Tandem Mass Spectrometry; Esters; tandemová hmotnostní spektrometrie; Bile Acids and Salts; estery; střevní mikroflóra; žlučové kyseliny a soli; kyselina chenodeoxycholová; Chenodeoxycholic Acid; lidé